Assessing Temperament Risk Factors in Late Childhood and Early Adolescence: Development and Validation of the Integrative Late Childhood Temperament Inventory. - Biedermann, Vivienne; Zentner, Marcel (Child Psychiatry & Human Development, 2026)
Childhood temperament has a well-documented influence on later life outcomes, notably behavior problems, quality of interpersonal relationships, and academic achievement. However, there is at present a lack of brief measures that assess temperament characteristics which are represented across models of temperament in the late childhood and early adolescence period. To redress this gap, the aim of the current study was to develop and validate a short questionnaire that extends an earlier integrative measure of temperament, the Integrative Child Temperament Inventory (ICTI) to the late childhood period. The new measure (named Integrative Late Childhood Temperament Inventory, ILCTI) includes all five components of the ICTI (frustration, behavioral inhibition, attention/persistence, activity level, sensory sensitivity), plus affiliation. German- or English-speaking parents rated a total of 525 children, aged 8 to 14 years. Confirmatory factor analyses supported the predicted structure of the new measure. Examination of fit indices and psychometric analyses showed that 24 items are sufficient to capture all six dimensions reliably. Next to convergent validity with established measures of temperament and personality, we also present analyses of associations with measures of externalizing problems, internalizing problems, and school failure all of which support the instrument's clinical utility. Thus, despite its brevity, the ILCTI is a reliable and valid measure of late childhood temperament that can be helpful in assessing risk of developing behavior problems or school failure.